Segmental Spinal Dysgenesis - Nisar Ahmed; Rahat Shahid; Kiran Nauman; Nauman Ayub (Journal of Bahria University Medical and Dental College)
We report a rare case of segmental spinal dysgenesis in a nine months old boy. The boy was born with flaccid paraplegia and lower limb deformities. Radiological workup revealed severe vertebral and spinal cord anomalies resulting into kyphosis and neurological deficits leading to grave disability and morbidity. The aim of reporting this case is to highlight the role of magnetic resonance imaging in the diagnosis of extent of spinal abnormalities for surgical correction.